(untitled) (Research, Society and Development, 2022)
Chikungunya fever (CF) is an arbovirosis caused by the Chikungunya virus (CHIKV). The main characteristic of CF is joint pain and more than half of infected patients experience chronic conditions. This case series study evaluated the persistent musculoskeletal presentations of CF in a sample of 72 patients with persistent symptoms (≥1 month) after CF confirmed by laboratory tests (detection of CHIKV by polymerase chain reaction [PCR] and/or immunoglobulin [Ig]M and/or IgG). The patients were followed up for 12 months after treatment at the outpatient clinic of the University Hospital of the Federal University of Sergipe (Hospital Universitário da Universidade Federal de Sergipe - HU/UFS). They were evaluated at admission and after 1 month, 2 months, and then every 3 months for up to 12 months. Painful and/or swollen joints, periarticular symptoms, other important findings on physical examination, and visual analogue pain scale (VAS) were evaluated during all consultations. Main results: Among the patients evaluated, 84.7% were female, the mean age was 53.8 years, and the mean duration of musculoskeletal complaints was 6 months. Comorbidities were present in 61.1% of patients and previous musculoskeletal disease was present in 69.4%. The most frequent presentation on admission was polyarticular, which occurred in 76.4% of cases. The most affected joints were the hands, knees, ankles, and feet. VAS on admission was intense in 66.7% of patients. Tenosynovitis was present in 44.5% of patients and was more frequently reported in the ankles. Corticosteroids and chloroquine were administered to 65.3% and 31.98% of patients, respectively. The findings indicated that persistent musculoskeletal presentations occur frequently after CF. These results provide a better understanding of patient profiles, musculoskeletal involvement, and CF progression, and may guide effective strategies for therapeutic management.